COMPREHENSIVE LITERATURE ANALYSIS ON SOCIAL INCLUSION FOR PERSONS WITH DISABILITIES IN INDONESIA - Enung Huripah (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Social inclusion for people with impairments is a vital step towards creating an equitable and fair society. Using the Comprehensive Literature Review technique, this study will examine the policies, problems, and supporting factors in the implementation of social inclusion for people with disabilities in Indonesia. The findings demonstrate that Indonesia already has a number of supportive laws, such as Law No. 8/2016 on Persons with Disabilities, however there are still gaps in their implementation. The primary barriers are a lack of accessible infrastructure, a shortage of qualified personnel, and a persistent societal stigma associated with persons with impairments. Government commitment, the engagement of civil society organisations, and the deployment of adaptive technology all help to promote social inclusion. The report also examines social inclusion methods in other countries, such as Sweden and Japan, where progressive policies have been effectively implemented via government-private sector partnership. The findings of this research emphasise the need of a multidisciplinary approach to social inclusion, as well as the need for more systematic tactics such as greater policy supervision, technology optimisation, and cross-sector cooperation. With these approaches, social inclusion for individuals with disabilities in Indonesia may be achieved in an efficient and sustainable manner.